Studying the Effect of Growth Regulator Naphthalene Acetic Acid (NAA) and Boron Element on Fruitset and Production of (Washington Navel) Citrus sinensis L. Osbeck - ديب, علي; صهيوني, فهد; جعفر, رائد (Latakia University Journal -Biological Sciences Series, 2021)
This study was conducted during 2019 on orange trees navel variety located in Al_Shir village in Lattakia, in aim of reducing fruit fall phenomenon witch spread in the region and improving production, through using foliar spray with naphthalene acetic acid (NAA) at (10 and 20 PPm) concentrations. And borax in concentrations (50 and 100 PPm), singly and mixed. The results showed that each of two treatments, T5 (Boron 100 PPm) and T7 (Boron 100 PPm + NAA 10 PPm), outperformed in fruitset percentage on the rest treatments, including the control, the fruitset percentage reached to (40.10 -38.34%) respectively, and spraying a solution of NAA with (20 ppm) concentration (T3) gave the best fruit retention percentage outperforming all treatments, and it was found that spraying with a higher concentration (20 PPm) of NAA mixed with a higher concentration (100 PPm) of boron (T7) gave the best yield (100.43 kg / tree), outperforming all the treatments, including the control (T1), where the quantity of production in it didn't exceed (47.16 kg / tree)